Genetic variation in the lactase gene, dairy product intake and risk for prostate cancer in the European prospective investigation into cancer and nutrition - Travis, R; Appleby, P; Siddiq, A; Allen, N; Kaaks, R; Canzian, F; Feller, S; Tjønneland, A; Føns Johnsen, N; Overvad, K; Ramõn Quirõs, J; González, C; et al. (2013)
High dairy protein intake has been found to be associated with increased prostate cancer risk in the European Prospective Investigation into Cancer and Nutrition (EPIC). To further examine this possible relationship, we investigated the hypothesis that a genetic polymorphism in the lactase (LCT) gene might be associated with elevated dairy product intake and increased prostate cancer risk in a case-control study nested in EPIC. The C/T-13910 lactase variant (rs4988235) was genotyped in 630 men with prostate cancer and 873 matched control participants. Dairy product consumption was assessed by diet questionnaire. Odds ratios (ORs) for prostate cancer in relation to lactase genotype were estimated by conditional logistic regression. Lactase genotype frequency varied significantly between countries, with frequencies of the T (lactase persistence) allele ranging from 7% in Greece to 79% in Denmark. Intake of milk and total dairy products varied significantly by lactase genotype after adjustment for recruitment center; adjusted mean intakes of milk were 44.4, 69.8 and 82.3 g/day among men with CC, CT and TT genotypes, respectively. The lactase variant was not significantly associated with prostate cancer risk, both in our data (adjusted OR for TT vs. CC homozygotes: 1.10, 95% CI: 0.76-1.59) and in a meta-analysis of all the published data (combined OR for T allele carriers vs. CC homozygotes: 1.12, 0.96-1.32). These findings show that while variation in the lactase gene is associated with milk intake in men, the lactase polymorphism does not have a large effect on prostate cancer risk. What's new? High dairy protein intake has previously been found to be associated with increased prostate cancer risk in the European Prospective Investigation into Cancer and Nutrition (EPIC). The current study was nested in EPIC, and results from this first Europe-wide study suggest that while the C/T13910 lactase polymorphism is associated with milk intake, the variant has no large effect on prostate cancer risk. The data illustrate the challenges of applying mendelian randomisation to explore the relationship between dairy product consumption and cancer risk. Very large studies with both genetic and dietary data are thus needed for investigations using genetic proxies of nutritional exposures. Copyright © 2012 UICC.